2021
DOI: 10.1039/d1cc00374g
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite-enhanced copper-based Fenton reactions for biofilm removal

Abstract: Unwanted biofilms present challenges for many industries. Herein an innovative biofilm removal technology was developed based on nitrite-accelerated Fenton chemistry, where both dissolved Cu ions and nano-CuO surfaces efficiently generate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Wang et al. [ 59 ] recently revealed that nitrite might accelerate the redox cycle of Cu(II) into Cu(I), which can be used to improve biofilm destruction using copper‐based Fenton reactions. The non‐further increase of the pararosaniline degradation rate with increasing nitrite dosage from 1 to 10 × 10 −3 m may be explained in the same way that an excess of H 3 NOH + , where the radicals quench by NO 2 − [Equations (21) and (22)] is becoming the dominating mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al. [ 59 ] recently revealed that nitrite might accelerate the redox cycle of Cu(II) into Cu(I), which can be used to improve biofilm destruction using copper‐based Fenton reactions. The non‐further increase of the pararosaniline degradation rate with increasing nitrite dosage from 1 to 10 × 10 −3 m may be explained in the same way that an excess of H 3 NOH + , where the radicals quench by NO 2 − [Equations (21) and (22)] is becoming the dominating mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that nitrite may serve as a ferric ion reductant, similar to hydroxylamine, albeit with a lower reduction due to the larger rate constant between NO 2 − and • OH (k = 1 × 10 10 m −1 s −1 , compared to <1 × 10 10 m −1 s −1 for the reaction of H 3 NOH + with • OH). Wang et al [59] recently revealed that nitrite might accelerate the redox cycle of Cu(II) into Cu(I), which can be used to improve biofilm destruction using copper-based Fenton reactions. The non-further increase of the pararosaniline degradation rate with increasing nitrite dosage from 1 to 10 × 10 −3 m may be explained in the same way that an excess of H 3 NOH + , where the radicals quench by NO 2 − [Equations ( 21) and ( 22)] is becoming the dominating mechanism.…”
Section: Effects Of Mineral Anions and Natural Organic Mattermentioning
confidence: 99%